Strategi Inovasi Produk Dan Efesiensi Operasional Terhadap Kinerja Umkm (Survei Pada UMKM Makanan Di Kota Sukabumi) - Mahesa Saputra; R. Deni Muhammad Danial; Nor Norisanti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Food MSMEs are an industrial sector that can be relied on as an indicator of economic stability at both the local and regional levels. The function of MSMEs is not only to drive business, but also to empower society in general. This research aims to determine the influence of product innovation strategies and operational efficiency on the performance of food MSMEs in Sukabumi City. This research uses descriptive and associative methods with a quantitative approach. The sampling technique in this research used the Slovin technique, with a sample size of 100 food MSMEs as respondents. Semantic differential is used as a scale, and the data analysis techniques used in this research are the classical test, multiple correlation coefficient, coefficient of determination, multiple linear regression, and hypothesis testing simultaneously (F test) and partially (T test). Furthermore, the data that has been obtained will be carried out various tests such as validity and reliability tests and classical assumption tests will be carried out and then analyzed with various tests with the help of SPSS 25 software in an effort to answer the hypothesis in this research. The research results show that product innovation strategy has a significant influence on the performance of food MSMEs in the city of Sukabumi, as well as operational efficiency has a significant influence on the performance of food MSMEs in the city of Sukabumi.